2000
DOI: 10.1080/02705060.2000.9663735
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Microhabitat Selection by Brown Trout in the Linthkanal, a Mid-Sized River

Abstract: T e Linthkanal, a medium sized artificial river canal (mean discharge ' 1 55 m3 s-), does not fit the usual concept of a s awning water for brown trout.Nevertheless, during the spawning seasons of 1 8 9511996 and 199611997 100 -150 redds were observed. Microhabitat parameters such as depth, current velocity, bottom substrate com osition, and proportion of fine sediment at both spawning and random sites had \ een measured. At the spawning sites mean values for current velocity were 56 cm s-1 and for depth 159 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
(11 reference statements)
4
6
0
Order By: Relevance
“…() and Zimmer & Power () found the same values for bottom velocities as presented in this study. Concerning mean velocity, Schneider () and Walker & Bayliss () recorded values similar to those in this study. In general, the data recorded in this study cover almost the whole range of reported velocities for spawning brown trout.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…() and Zimmer & Power () found the same values for bottom velocities as presented in this study. Concerning mean velocity, Schneider () and Walker & Bayliss () recorded values similar to those in this study. In general, the data recorded in this study cover almost the whole range of reported velocities for spawning brown trout.…”
Section: Resultssupporting
confidence: 88%
“…Combining all study rivers, collected data shows use of a depth range of 9-41 cm. Consequently, the water depth range in our study largely covered the data reported in the literature, except for Schneider (2000) and Wollebaek et al (2008). These differences can be linked to river size and female size.…”
Section: Analysis Of Habitat Use and Burial Depths In Comparison To Psupporting
confidence: 66%
“…The trout spawn on stone and gravel bottoms, usually in running waters, although lake spawning populations occur occasionally (Klemetsen 1967;Scott & Irvine 2000;Sneider 2000;Brabrand et al 2002). The species reproduces in autumn or winter; the earlier the higher the latitude and altitude because of lower water temperature and longer egg incubation period.…”
Section: Life Cycle and Habitat Usementioning
confidence: 99%
“…Area below dotted straight line is measured (cross symbol) and estimated concentrations in Swiss rivers (unpublished data LHG and NADUF). Below straight line, no LC (lethal concentrations) was found (Herbert et al 1961;Alabaster and Lloyd 1980;Newcombe and MacDonald 1991;Newcombe and Jensen 1996;Berry et al 2003) al (Baglinière and Maisse 2002;Zimmer and Power 2006) and the redds are usually placed at the same sites in subsequent years (Schneider 2000). For redd construction female trout excavate a depression by removing fines and gravel creating a typical pit and tail structure.…”
Section: Habitat Requirements Of Gravel-spawning Brown Troutmentioning
confidence: 99%